(untitled) (Hoboken, N.J., 2013)
Molecular Microbial Ecology of the Rhizosphere covers current knowledge on the molecular basis of plant-microbe interactions in the rhizosphere. Also included in the book are both reviews and research-based chapters describing experimental materials and methods. Edited by a leader in the field, with contributions from authors around the world, Molecular Microbial Ecology of the Rhizosphere brings together the most up-to-date research in this expanding area, and will be a valuable resource for molecular microbiologists and plant soil scientists, as well as upper level students in microbiology, ecology, and agriculture.
Keywords: Microbial Interactions,Soil microbiology,Tương tác vi sinh vật,Vi sinh học đất